Penggunaan Microsite dalam Mendukung Kegiatan Perlombaan Tingkat Mahasiswa Forum Komunikasi Pimpinan FKIP Negeri se-Indonesia - Saprudin Saprudin; Jainudin Abdullah; Abdu Mas’ud; Fatma Hamid; Nurdin Abdul Rahman; Aji Saputra; Usman Sambiri; Astuti Salim; Indry Widyasti Anwar; Haerul Haerul; Yetti Yetti; Mukhtar Yusuf; Yusmar Yusuf; Darmawati Hady (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2024)
In 2023, FKIP Universitas Khairun has successfully hosted the summit of the Forum Komunikasi (Forkom) FKIP Negeri se-Indonesia which was also enlivened by the implementation of 7 categories of student level competitions. One of the problems faced is the need for publication media and competition administration management. Community service activities were carried out to resolve these problems which included preliminary survey activities, designing a competition microsite that was integrated with Google Drive, mentoring and evaluation. Data on competition participants' responses was collected through a questionnaire distributed to a sample of 30 competition participants. The questionnaire was distributed using Google Forms. The results of the service show that the use of a microsite integrated with Google Drive can provide easy access to competition information and can be used as a medium for documenting competition administration documents so that competition implementation becomes more effective and efficient. In general, competition participants gave very good responses to the implementation of the competition.